Incorporating insulin into alginate-chitosan 3D-printed scaffolds: A comprehensive study on structure, mechanics, and biocompatibility for cartilage tissue engineering - Afsaneh Jahani; Mohammad Sadegh Nourbakhsh; Ali Moradi; Marzieh Mohammadi; Lobat Tayebi (Carbohydrate Polymer Technologies and Applications)
Osteoarthritis is a leading cause of disability worldwide, challenging current treatments to limited cartilage self-healing capacity. Cartilage tissue engineering (CTE) integrates cells, scaffolds, and signaling molecules, with Insulin being utilized as a differentiation biomolecule due to cost-effectiveness, dose-dependent influence on chondrogenesis, suitable biological activity, and ability to activate relevant receptors. Yet, administering differentiation biomolecules through conventional scaffolds poses a persistent challenge. Alginate (Alg) is commonly employed in CTE for its biocompatibility, though it lacks sufficient mechanical properties. Chitosan (Cs), while enhancing scaffold mechanical properties, but does not independently provide optimal support for chondrogenesis. While Alg-Cs scaffolds have garnered attention, challenges persist in achieving sustained differentiation biomolecules delivery and attaining suboptimal structural and biological properties for cartilage regeneration. This study utilizes advanced scaffolds by employing three dimensional (3D) printing technique to create Insulin-loaded Alg-Cs scaffolds, examining their structural, mechanical, and release properties, and assessing cell viability and chondrogenic differentiation through markers like COL1A1, COL2A1, SOX9 and ACAN. Following a 30-day implantation period, we also evaluate histological parameters. The findings revealed that the incorporation of a 20 (μg/ml) dose of Insulin into Alg-Cs 3D-printed scaffolds significantly enhanced the expression of these markers, indicating improved chondrogenic potential for cartilage regeneration. Histological analysis confirmed favorable biocompatibility and structural integrity of Insulin-loaded pure Alg and Alg-Cs scaffolds at drug loading levels of up to 20 and 10 μg, respectively. The hypothesis suggests that these advanced scaffolds can achieve controlled Insulin release, enhancing cartilage regeneration. This research aims to develop to yield mechanically optimized, bioactive 3D-printed scaffolds for regulated delivery of Insulin to promote cartilage regeneration.